Nanoengineering InP Quantum Dot-Based Photoactive Biointerfaces for Optical Control of Neurons - Karatum, Onuralp; Aria, Mohammad Mohammadi; Eren, Guncem Ozgun; Yildiz, Erdost; Melikov, Rustamzhon; Srivastava, Shashi Bhushan; Surme, Saliha; Dogru, Itir Bakis; Bahmani Jalali, Houman; Ulgut, Burak; Sahin, Afsun; Kavakli, Ibrahim Halil; et al. (Frontiers in Neuroscience, 2021)
Light-activated biointerfaces provide a non-genetic route for effective control of neural activity. InP quantum dots (QDs) have a high potential for such biomedical applications due to their uniquely tunable electronic properties, photostability, toxic-heavy-metal-free content, heterostructuring, and solution-processing ability. However, the effect of QD nanostructure and biointerface architecture on the photoelectrical cellular interfacing remained unexplored. Here, we unravel the control of the photoelectrical response of InP QD-based biointerfaces via nanoengineering from QD to device-level. At QD level, thin ZnS shell growth (~0.65 nm) enhances the current level of biointerfaces over an order of magnitude with respect to only InP core QDs. At device-level, band alignment engineering allows for the bidirectional photoelectrochemical current generation, which enables light-induced temporally precise and rapidly reversible action potential generation and hyperpolarization on primary hippocampal neurons. Our findings show that nanoengineering QD-based biointerfaces hold great promise for next-generation neurostimulation devices.